A tournament, not a competition - Grigoryeva, Elena; Chernikhov, Andrey (project baikal, 2023)
On May 27, 2023, the jubilee V Tournament of Architectural Graphics “Line of Thought”, established by the Iakov Chernikhov International Foundation in 2018, was held within the framework of the XXVIII International Exhibition of Architecture and Design “ARCH MOSCOW”. The aim of the Tournament is to support the art of hand-made graphics. The prize, the Silver Stylus, was unexpectedly awarded to Marianna Antonova, a beginning architect from St. Petersburg. Architect Andrey Chernikhov, the author of the idea and the President of the Iakov Chernikhov International Foundation, will tell us what the Graphics Tournament is all about.